Kearifan dan Manifestasinya Pada Tokoh-Tokoh Lanjut Usia - Basri, Augustine Sukarlan (UI Scholars Hub, 2006)
This study tried to identify the characteristics and factors of wisdom using three age groups: young adult, middle adult, and elderly. Forty three characteristics were established. Factor analysis and one-way analysis of variance were used and 5 factors were found: (1) Spiritual-Moral Condition; (2) Interpersonal Relationship Ability; (3) Judgment and Decision Making Ability; (4) Personal Condition; and (5) Exceptional/Specific Ability. Spiritual-Moral Condition was a unique factor that former researches did not mention this condition as a factor of wisdom. This condition was also judged as the prime contributor to describe wisdom. Using interview, this study also described the unique manifestations of the five factors of wisdom in the life of three elderly people judged as wise persons by the respondents.